Fertilizer, and method of producing the same

JP2025036307AActive Publication Date: 2025-03-14SANYO CHEM IND LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024146561
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-29
Filing Date
2024-08-28
Publication Date
2025-03-14
Estimated Expiration
2044-08-28

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、安全かつ簡便な方法により得られる肥料及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036307000001
    Figure 2025036307000001
  • Figure 2025036307000002
    Figure 2025036307000002
  • Figure 2025036307000003
    Figure 2025036307000003
Patent Text Reader

Abstract

To provide a fertilizer that can be obtained by a safe and simple method, and a method of producing the same.SOLUTION: The fertilizer includes a substance containing a phosphate of low solubility, and a high molecular weight compound comprising a carboxy group and / or a carboxylate group in its molecule, in which the total amount of the carboxy group and the carboxylate group, is not less than 5 mmol / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fertilizer and a method for producing the same. [Background technology]

[0002] Phosphorus, along with nitrogen and potassium, is a nutrient necessary for plant growth, and is often supplied by applying chemical fertilizers to farmland. In recent years, from the viewpoint of reducing the environmental load and economically producing phosphorus fertilizer, the recovery of water-soluble phosphoric acid from waste materials such as sludge incineration ash, sludge, soil (including industrial waste soil and greenhouse horticulture waste soil), steelmaking slag, livestock manure, and food waste, and use of the recovered phosphoric acid as fertilizer has been considered. When recovering phosphoric acid using conventional techniques, a step of making the pH of the target to be treated acidic or alkaline may be required (see Patent Document 1,

[0003] (See, for example, US Pat. No. 6,393,626.) Equipment used in such processes is prone to corrosion, and processes involving such processes raise safety concerns for personnel involved in phosphate recovery operations. Furthermore, since the target material whose pH has become acidic or alkaline cannot be released into the environment as is, it is necessary to neutralize the target material whose pH has become acidic or alkaline. Therefore, there is a demand for improvements in the technology for recovering phosphate in terms of simplification, and studies are being conducted on this matter (see Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5664995 Summary of the Invention [Problem to be solved by the invention]

[0004] According to the method described in the above Patent Document 1, phosphoric acid can be recovered by blowing carbon dioxide into an aqueous suspension of incineration sludge containing heavy metals, followed by solid-liquid separation and recovery of the filtrate. Thus, according to the method described in Patent Document 1, phosphoric acid can be recovered in a simpler manner than conventional techniques. However, this method requires the steps of preparing an aqueous suspension of incineration sludge, blowing in carbon dioxide, and performing solid-liquid separation, and there is room for improvement in terms of simplification. An object of the present invention is to provide a fertilizer that can be obtained by a method that is safer and simpler than conventional methods, and a method for producing the same. [Means for solving the problem]

[0005] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention is as follows. [1] A fertilizer comprising a substance containing poorly soluble phosphate and a polymeric compound having a carboxyl group and / or a carboxylate group within the molecule, wherein the total amount of the carboxyl group and the carboxylate group contained in the polymeric compound having a carboxyl group and / or a carboxylate group within the molecule is 5 mmol / g or more. [2] The fertilizer according to [1], wherein the polymeric compound having a carboxyl group and / or a carboxylate group in the molecule is a polymer containing structural units derived from (meth)acrylic acid and / or a (meth)acrylate salt. [3] A fertilizer according to [1] or [2], further comprising water. [4] A method for producing a fertilizer, comprising step 1 of mixing a substance containing a poorly soluble phosphate with a component containing a polymeric compound having a carboxyl group and / or a carboxylate group in its molecule, wherein the total amount of the carboxyl group and the carboxylate group contained in the polymeric compound having a carboxyl group and / or a carboxylate group in its molecule is 5 mmol / g or more. [5] The method for producing a fertilizer according to [4], wherein the polymer compound having a carboxy group and / or a carboxylate group in the molecule is a polymer containing structural units derived from (meth)acrylic acid and / or a (meth)acrylate salt. [6] A method for producing a fertilizer according to [4] or [5], further comprising adding water to the components and mixing them in step 1. [7] The method for producing a fertilizer according to [6], further comprising a step of allowing the mixture obtained by adding water to and mixing the components in step 1 to stand at a temperature condition of 10°C to 80°C. Effect of the Invention

[0006] According to the present invention, it is possible to provide a fertilizer that can be obtained by a safe and simple method, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] <fertilizer> The fertilizer of the present invention comprises a substance containing a poorly soluble phosphate and a polymer compound having a carboxy group and / or a carboxylate group in its molecule, and the total amount of the carboxy group and the carboxylate group contained in the polymer compound having a carboxy group and / or a carboxylate group in its molecule is 5 mmol / g or more. In this specification, a carboxy group and / or a carboxylate salt group is also referred to as a "carboxylic acid (salt) group".

[0008] In the present invention, the substance containing poorly soluble phosphate is not particularly limited as long as it contains poorly soluble phosphate. Examples of the substance containing poorly soluble phosphate include phosphate compounds such as aluminum phosphate, iron (III) phosphate dihydrate, and tricalcium phosphate; soil, rice bran, rice husk, rice husk carbonized material, livestock feces (cow feces, pig feces, chicken feces), carbonized livestock feces, sludge, sludge incineration ash, steel slag, and food waste, and other resources.

[0009] In the present invention, the term "poorly soluble phosphate" refers to all phosphates other than water-soluble phosphates. In the present invention, the term "water-soluble phosphate" refers to a phosphate that is dissolved in water at 25°C. In the present invention, "dissolved in water at 25°C" means "dissolves in an amount of 0.1 mg or more in 1000 g of water at 25°C."

[0010] In the present invention, the polymer compound having a carboxylic acid (salt) group in the molecule has a total amount of carboxyl groups and carboxylate groups of 5 mmol / g or more. When the total amount of carboxyl groups and carboxylate groups in the compound is 5 mmol / g or more, the effect of solubilizing the poorly soluble phosphate in a substance containing the poorly soluble phosphate is sufficiently exhibited. If a polymer compound having a carboxylic acid (salt) group but a total amount of carboxyl groups and carboxylate groups of less than 5 mmol / g is used, the effect of solubilizing the poorly soluble phosphate in a substance containing the poorly soluble phosphate is not sufficiently exhibited. From the viewpoint of being excellent in the effect of solubilizing poorly soluble phosphates in a substance containing poorly soluble phosphates, the polymer compound having a carboxylic acid (salt) group in the molecule is preferably one in which the total amount of carboxyl groups and carboxylate salt groups is 9 mmol / g or more, and more preferably 10 mmol / g or more.

[0011] The amount of carboxylic acid (salt) groups contained in a polymer compound having a carboxylic acid (salt) in the molecule can be determined by the following method. (1) Place a sample in a beaker and accurately weigh out its weight (1 g). Add 50 ml of ion-exchanged water and stir to dissolve or swell the sample to obtain a sample solution. (2) Immerse the electrodes of the potentiometric titrator in the sample solution and, while stirring, add dropwise a mixture of first-grade reagent hydrochloric acid (35%) and ion-exchanged water (35% hydrochloric acid:ion-exchanged water = 1:1) to adjust the pH of the sample solution to below 3. (3) Add 0.1 mol / L potassium hydroxide methanol standard solution little by little, stir until the potential difference becomes constant, and record the potential difference and the amount of dripping when the potential difference becomes constant. Repeat this operation until the end point is passed. The endpoint is determined by plotting the amount of standard solution dropped and the potential difference on a graph paper, and the inflection point of the titration curve is determined as the endpoint. (4) Repeat steps (1) to (3) for two samples, and also perform a blank test. The total amount of carboxyl groups and carboxylate groups contained in the molecule is calculated from the following formula, and the average value of the two samples is regarded as the total amount of carboxyl groups and carboxylate groups contained in the molecule (mmol / g). Amount of carboxyl groups and carboxylate groups contained in the molecule (mmol / g) = (AB) × f × 0.1 / S A: The amount (ml) of 0.1 mol / L potassium hydroxide methanol standard solution required for this test B: Amount of 0.1 mol / L potassium hydroxide methanol standard solution dropped for blank test (ml) f: Potency of 0.1 mol / L potassium hydroxide methanol standard solution S: Sample amount (g)

[0012] Examples of the polymer compound having a carboxylic acid (salt) in the molecule used in the present invention include a polymer containing a structural unit derived from (meth)acrylic acid and / or a (meth)acrylate salt (also referred to as "polymer X"). In this specification, acrylic acid and / or (meth)acrylic acid salts are also referred to as "acrylic acid (salt)".

[0013] The polymer X contains a structural unit derived from (meth)acrylic acid (salt). Examples of the (meth)acrylic acid (salt) that is a structural unit of the polymer X include acrylic acid, acrylic acid salts, methacrylic acid, methacrylic acid salts, and combinations thereof. In the present invention, (meth)acrylic acid means methacrylic acid and / or acrylic acid. Examples of the salt include alkali metal (lithium, sodium (also written as Na), potassium, etc.) salts, alkaline earth metal (magnesium, calcium, etc.) salts, and ammonium (NH4) salts. Among these salts, from the viewpoint of absorption characteristics, alkali metal salts and ammonium salts are preferred, more preferably alkali metal salts, and even more preferably sodium salts.

[0014] Specific examples of polymer X include polyacrylic acid, polyacrylic acid salts, polymethacrylic acid, polymethacrylic acid salts, copolymers of (meth)acrylic acid (salts) and starch, and copolymers of (meth)acrylic acid (salts) and other monomers.

[0015] The starch constituting the copolymer of (meth)acrylic acid (salt) and starch is not particularly limited, and examples thereof include wheat starch, rice starch, corn starch, potato starch, and the like.

[0016] The other monomer constituting the copolymer of (meth)acrylic acid (salt) and other monomer means a monomer other than (meth)acrylic acid (salt), and specifically includes (meth)acrylic acid esters having a hydroxy group, an alkyl group, a polyoxyalkylene group, or the like, such as 2-hydroxyethyl (meth)acrylate, n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polybutylene glycol mono(meth)acrylate, and methoxypolyethylene glycol mono(meth)acrylate, 2-vinylpyridine, 4-vinylpyridine, diethylaminoethyl methacrylate, dipropylaminoethyl methacrylate, dimethylaminopropyl (meth)acrylamide, allyl dimethylamine, allyl diethylamine, allyl dipropylamine, (meth)acrylic dimethylamine, (meth)acrylic diethylamine, (meth)acrylic dipropylamine, and acrylamidopropyl trimethylamine. Examples of the vinyl monomer include cationic vinyl monomers such as methyl ammonium chloride, methacrylamide propyl trimethyl ammonium chloride, methacrylic acid dimethylamino methyl ethyl chloride, dimethylamino ethyl methacrylate, N-methacryloyloxyethyl-N,N-dimethyl ammonium-α-N-methyl carboxybetaine, and dimethyl diallyl ammonium chloride; anionic vinyl monomers such as itaconic acid, aconitic acid, hydroxyacrylic acid, maleic anhydride, fumaric acid, vinyl sulfonic acid, allyl sulfonic acid, (meth)acrylic acid sulfonic acid, styrene sulfonic acid, 2-acrylamido-2-methylpropane sulfonic acid, and acrylamido dimethylpropane sulfonic acid; vinyl esters such as vinyl acetate and vinyl propionate; olefins such as ethylene, propylene, isobutylene, vinyl chloride, and vinylidene chloride; styrene-based monomers such as styrene and α-methylstyrene; diene-based monomers such as butadiene, isoprene, and chloroprene; and nitrile-based monomers such as acrylonitrile and methacrylonitrile.

[0017] The polymer X may be a crosslinked polymer. Examples of the crosslinking agent constituting the crosslinked polymer include N,N'-methylenebis(meth)acrylamide, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, glycerin di(meth)acrylate, glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, triallylamine, triallyl cyanurate, triallyl isocyanurate, tetraallyloxyethane, pentaerythritol triallyl ether, ethylene glycol diglycidyl ether, glycerin diglycidyl ether, and sorbitol polyglycidyl ether.

[0018] The amount of the crosslinking agent can be appropriately selected depending on the desired crosslinking density, and may be, for example, 0.005 mol % or more, or 0.5 mol % or more, and 2.0 mol % or less, or 1.5 mol % or less, relative to the monomers constituting the crosslinked polymer.

[0019] The polymer X can be produced, for example, by a method including a step of obtaining a polymer (polymerization step) by polymerizing (solution polymerization, emulsion polymerization, suspension polymerization, or the like) a composition containing monomer components that are structural units [(meth)acrylic acid (salt) and other monomers used as necessary], a solvent, a polymerization initiator, and components used as necessary (crosslinking agent, neutralizing agent, or the like), a step of drying the polymer, and a step of further neutralizing the polymer with a neutralizing agent as necessary.

[0020] It is preferable that the acid group of the structural unit constituting the polymer X [for example, a carboxy group of a structural unit derived from an acid group-containing monomer such as (meth)acrylic acid] is partially neutralized with a base from the viewpoint of easily releasing phosphate ions and / or available phosphoric acid by solubilizing poorly soluble phosphate salts. As the base for neutralization, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, or an alkali metal carbonate such as sodium carbonate, sodium bicarbonate or potassium carbonate can be used. In the production of the polymer X, the neutralization may be performed at any timing among before the start of the polymerization step, during the polymerization step, after the polymerization step, or a combination thereof. Specifically, there are a method of neutralizing the acid group-containing monomer before the polymerization step, and a method of neutralizing the polymer obtained after the polymerization in the form of a hydrous gel.

[0021] As the polymer compound having a carboxylic acid (salt) in the molecule, from the viewpoint of easily solubilizing poorly soluble phosphate salts and liberating phosphate ions and / or available phosphoric acid, a polymer containing a structural unit derived from (meth)acrylic acid (salt) is preferable, and a polyacrylic acid (salt) is more preferable.

[0022] The fertilizer of the present invention contains a substance containing poorly soluble phosphate and a polymeric compound having a carboxylic acid (salt) group in the molecule. When the fertilizer of the present invention is used in an environment where water is provided, the substance containing poorly soluble phosphate and the polymeric compound having a carboxylic acid (salt) group in the molecule contained in the fertilizer mix with water, so that the poorly soluble phosphate in the substance is solubilized, and phosphate ions and / or available phosphoric acid are liberated. The phosphate ions and available phosphoric acid are components that can be absorbed by plants and function as a fertilizer. In other words, according to the present invention, phosphate ions and / or available phosphate can be liberated simply by using the product in an environment where water is provided, thereby enabling the product to function as a fertilizer in a simple and safe manner.

[0023] The amount of the polymeric compound having a carboxylic acid (salt) group in the molecule to be mixed is preferably 0.01 to 200 parts by weight, and more preferably 0.1 to 100 parts by weight, per 100 parts by weight of the substance containing the poorly soluble phosphate, from the viewpoint of easily solubilizing the poorly soluble phosphate.

[0024] The fertilizer of the present invention may be one obtained by further mixing water with a substance containing poorly soluble phosphate and a polymeric compound having a carboxylic acid (salt) group in the molecule. In such an embodiment, since water is mixed, the substance containing poorly soluble phosphate and the polymeric compound having a carboxylic acid (salt) group in the molecule contained in the fertilizer are mixed with water, so that the poorly soluble phosphate in the substance is solubilized, and phosphate ions and / or available phosphoric acid are liberated, so that the fertilizer functions as it is.

[0025] When the fertilizer of the present invention is an embodiment in which water is further mixed with a substance containing a poorly soluble phosphate and a polymer compound having a carboxylic acid (salt) group in the molecule, the amount of water mixed is preferably 10 to 50,000 parts by weight, and more preferably 1,000 to 30,000 parts by weight, per 100 parts by weight of the substance containing a poorly soluble phosphate, from the viewpoint of facilitating the mixing operation.

[0026] The fertilizer of the present invention may contain other components in addition to the above-mentioned components (a poorly soluble phosphate-containing substance, a polymeric compound having a carboxylic acid (salt) group in the molecule, and water used as necessary). Such other components include nitrogen sources such as ammonium sulfate, ammonium chloride, ammonium nitrate, urea, Chilean saltpeter, and lime nitrogen, potassium sources such as wood ash, seaweed ash, potassium chloride, and potassium sulfate, and inorganic or organic soil improvement materials such as zeolite, activated carbon, vermiculite, perlite, peat moss, and coco peat.

[0027] <Fertilizer manufacturing method> The method for producing a fertilizer of the present invention includes a step 1 of mixing components including a substance containing a poorly soluble phosphate and a polymeric compound having a carboxylic acid (salt) group in its molecule, and the polymeric compound having a carboxylic acid (salt) group in its molecule has a total amount of carboxy groups and carboxylate salt groups of 5 mmol / g or more.

[0028] Step 1 is a step of mixing components containing a substance containing poorly soluble phosphate and a polymeric compound having a carboxylic acid (salt) group in the molecule. The poorly soluble phosphate-containing substance used in step 1 can be the same as the "substance containing poorly soluble phosphate" described in the "Fertilizer" section. The polymeric compound having a carboxylic acid (salt) group in the molecule used in step 1 can be the same as the polymeric compound having a carboxylic acid (salt) group in the molecule described in the "Fertilizer" section.

[0029] In step 1, the amount of the polymeric compound having a carboxylic acid (salt) group in the molecule is preferably 0.01 to 200 parts by weight, and more preferably 0.1 to 100 parts by weight, relative to 100 parts by weight of the substance containing the poorly soluble phosphate, from the viewpoint of easily solubilizing the poorly soluble phosphate.

[0030] In step 1, from the viewpoint of facilitating mixing and facilitating solubilization of the poorly soluble phosphate in the substance, it is preferable to further add water to and mix a component containing a substance containing a poorly soluble phosphate and a polymeric compound having a carboxylic acid (salt) group in its molecule. In step 1, the amount of water to be mixed is preferably 10 to 50,000 parts by weight, and more preferably 1,000 to 30,000 parts by weight, based on 100 parts by weight of the poorly soluble phosphate-containing substance.

[0031] The temperature conditions for carrying out step 1 can be set in consideration of the type and amount of the substance containing the poorly soluble phosphate, the type and amount of the polymer compound having a carboxylic acid (salt) group in the molecule, and the amount of water used as necessary, etc. From the viewpoint of facilitating the solubilization of the poorly soluble phosphate, step 1 is preferably carried out at a temperature condition of 10°C to 80°C.

[0032] From the viewpoint of sufficiently solubilizing the poorly soluble phosphate in the poorly soluble phosphate-containing substance, the method for producing a fertilizer of the present invention preferably includes a step (contact step) of contacting the poorly soluble phosphate-containing substance in the mixture with a polymeric compound having a carboxylic acid (salt) group in the molecule after mixing with water in step 1. Methods for contacting the poorly soluble phosphate-containing substance in the mixture with a compound having a carboxylic acid (salt) group in the molecule include a method of stirring the mixture obtained by performing step 1, a method of allowing the mixture obtained by performing step 1 to stand for a predetermined period of time, and the like.

[0033] The temperature conditions in the contact step can be set in consideration of the type and amount of the poorly soluble phosphate-containing substance, the type and amount of the polymer compound having a carboxylic acid (salt) group in the molecule, the amount of water, etc. The temperature conditions are preferably the same as those in step 1 (e.g., 10°C to 80°C) from the viewpoint of simplifying the apparatus. The contact time in the contact step is preferably 1 hour or more, more preferably 3 hours or more, and is preferably 240 hours or less, more preferably 168 hours or less, from the viewpoint of sufficiently solubilizing the poorly soluble phosphate in the substance containing the poorly soluble phosphate. As the contact step, a step of leaving the mixture obtained by carrying out step 1 at rest at a temperature condition of 10°C to 80°C is preferable from the viewpoint of a simple method.

[0034] When water is not mixed in step 1, the mixture of components containing the poorly soluble phosphate-containing substance obtained in step 1 and a polymeric compound having a total amount of carboxyl groups and carboxylate groups contained in the molecule of 5 mmol / g or more is used in an environment where water is provided, whereby the phosphate-containing substance and the polymeric compound having a carboxyl (salt) group in the molecule in the mixture mix with water, so that the poorly soluble phosphate in the substance is solubilized, and phosphate ions and / or available phosphoric acid are liberated. Thus, the mixture can function as a fertilizer when used in the presence of water.

[0035] When water is mixed in step 1, the mixed liquid after mixing with water or the mixed liquid after the contact step, if necessary, contains phosphate ions liberated from the poorly soluble phosphate and / or available phosphoric acid. Therefore, the mixed liquid can be used as a fertilizer as it is. The mixed liquid is filtered to obtain a liquid component, from which water is distilled off to obtain a solid material, which can be used as a fertilizer. Furthermore, a precipitate (calcium phosphate) obtained by adding a calcium salt (e.g., calcium hydroxide, calcium chloride, etc.) to the liquid component can be used as a fertilizer. EXAMPLES

[0036] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples unless it deviates from the gist of the present invention. In addition, unless otherwise specified, parts means parts by weight, and % means % by weight. The following temperatures include a range of ±2°C.

[0037] The components used in the examples and comparative examples are as follows. [Substance (A) containing poorly soluble phosphate: Also referred to as "Substance (A)"] (A-1) "Aluminum phosphate" (manufactured by Junsei Chemical Co., Ltd.) (A-2) "Iron(III) phosphate dihydrate" (Sigma-Aldrich) (A-3) "Tricalcium phosphate" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (A-4) "Rice husk charcoal" (manufactured by Luoyang Co., Ltd.) (A-5) "Chicken Manure Charcoal" (Take no Chikara, Rakuten Ichiba store) (A-6) "Soil" (brown lowland soil collected in Kyoto Prefecture that had been fertilized with chemical fertilizers for 20 years) (A-7) "Soil" (black soil collected in Saitama Prefecture) For the substance (A), the total phosphorus concentration and the water-soluble phosphorus concentration were measured by the method described below, and the weight ratio of water-soluble phosphorus based on the total phosphorus weight was calculated. The results are shown in Table 1.

[0038] [Polymer compound (B) having a total amount of carboxyl groups and carboxylate groups contained in the molecule of 5 mmol / g or more: [also referred to as compound (B)] (B-1) "Carribon L-400" [sodium polyacrylate, manufactured by Sanyo Chemical Industries, Ltd.: weight average molecular weight 10,000, solid content 43%] (B-2) Sodium polyacrylate obtained in Production Example 1 (B-3) Poly(sodium acrylate) crosslinked polymer obtained in Production Example 2 (B-4) Poly(sodium acrylate) crosslinked polymer obtained in Production Example 3 (B-5) Starch-acrylic acid copolymer obtained in Production Example 4 (B-6) Acrylic acid copolymer obtained in Production Example 5

[0039] [Compound (B') having a total amount of carboxyl groups and carboxylate groups contained in the molecule of less than 5 mmol / g: [also referred to as compound (B')] (B'-1) Sodium carboxymethyl cellulose (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B'-2) Acrylic acid copolymer obtained in Comparative Production Example 1 For compound (B) and compound (B'), the solid content and the amount of carboxylic acid (salt) group were calculated by the methods described below. The results are shown in Table 2.

[0040] <Method for measuring total phosphorus concentration in substance (A)> The total phosphorus concentration in the substance (A) was measured by the following method. The measurement target material was subjected to X-ray fluorescence analysis to measure the phosphorus content (mass%). The measured value was used to convert the total phosphorus concentration (mgP / g) in the material containing poorly soluble phosphates according to the following formula. [Total phosphorus concentration in substance (A) (mgP / g)] = [Phosphorus content (mass%)] x 10 For the substances (A) to be measured other than the reagents [(A-4), (A-5), (A-6), and (A-7)], the substances were ashed under the ashing conditions described below, and the results were converted to the composition ratios before ashing using the following formula. [Total phosphorus concentration in material (A) before incineration (mgP / g)] = [Total phosphorus concentration in material after incineration (mgP / g)] × [Remaining amount of incineration (%)] / 100 (Measurement conditions for fluorescent X-ray equipment: Common conditions for both ashed and non-ashed samples) Device name: Supermini200 [Rigaku Corporation] Method: Wavelength dispersion type Measurement method: SQX analysis (FP method) Sample measurement diameter: 30mm [Measurement conditions for (A-1), (A-2) and (A-3)] Measurement atmosphere: Helium Residual (main component): None Sample preparation method: Press molding or loose powder method Film used: PP (polypropylene film) Sample size: 2-3g [Measurement conditions for (A-4), (A-5), (A-6) and (A-7)] Measurement atmosphere: Vacuum Residual (main component): None Sample preparation method: Loose powder method Film used: PP Sample size: 2-3g [Ashing treatment of (A-4), (A-5), (A-6) and (A-7)] Of the substances (A) to be measured, those other than the reagents [(A-4), (A-5), (A-6) and (A-7)] were ashed in the following manner. (a) The sample was finely ground in a mortar. (b) The finely ground sample was pre-dried for 3 hours at 105°C using a circulating air dryer to obtain a pre-dried sample. (c) 10 g of the pre-dried sample was weighed out into an alumina crucible whose tare weight had been measured (referred to as S1). It was placed in an electric furnace and heated at 600°C for 1 hour, then at 1050°C for 1 hour. After cooling to room temperature (25°C), its weight was measured (G1). (d) The remaining amount of ash (%) was calculated using the following formula. Ashing remaining amount (%) = [{Weight after returning to room temperature (G1) - tare weight of crucible} / sample weight (S1)] x 100

[0041] <Method for measuring the concentration of water-soluble phosphorus in substance (A)> The concentration of water-soluble phosphorus contained in the substance (A) was determined by the following method. (1) 1 g of sample was mixed with 99 g of ion-exchanged water and left to stand at room temperature (25°C) for 3 hours. Using a 2.5 ml thermosyringe, the supernatant of the sample liquid after standing at room temperature was filtered through a 0.45 μm syringe filter, and the filtrate (of the sample) was collected. (2) 1.5 ml of the calibration curve aqueous solution (prepared using phosphate standard solution and diluted to 0.2 ppm, 0.5 ppm, 1 ppm, and 5 ppm as phosphate ion) was placed in the attached cell of Packtest(R) Phosphate / Phosphorus Phosphate WAK-PO4 (Kyoritsu Rikagaku Kenkyusho), 4 drops of the attached sulfuric acid were added, the cell was closed, and the cell was shaken 4 times to mix. (3) Following the instructions in the phosphoric acid pack test instructions, the sample was mixed with the color-developing solution in the individual package, the individual package was cut off with scissors, and the contents were returned to the cell. (4) The absorbance was measured 3 minutes after the calibration solution was sucked up. The measurement was performed under the following conditions using the following device. Absorbance measurement device: UV-1280 UV-Visible Spectrophotometer [Shimadzu Corporation] Measurement conditions: Photometric measurement, wavelength 650 nm, optical path length 5 mm (5) The absorbance of the sample filtrate was measured in the same manner as described in (2) to (4). At this time, any value exceeding the 5 ppm value on the calibration curve was diluted and remeasured so that the absorbance was between 0.2 ppm and 5 ppm. Values ​​below 0.2 ppm were considered to be below the detection limit. (6) The phosphate ion concentration in the sample filtrate was determined from the calibration curve. The concentration of water-soluble phosphorus contained in the substance containing poorly soluble phosphate was calculated by applying the above phosphate ion concentration to the following formula. [Phosphate concentration in filtrate (ppm)] = 31 × [Phosphate ion concentration in filtrate (ppm)] / 95

[0042] <How to calculate the weight ratio of water-soluble phosphorus based on the total phosphorus weight [100 x (water-soluble phosphorus / total phosphorus)]> The weight proportion of water-soluble phosphorus based on the total phosphorus weight in the substance (A) (referred to as "proportion of water-soluble phosphorus" in Table 1) was calculated from the following formula. Weight ratio of water-soluble phosphorus based on total phosphorus weight (%) = 100 × [Water-soluble phosphorus concentration in substances containing poorly soluble phosphates (mgP / g)] / [Total phosphorus concentration in substances containing poorly soluble phosphates (mgP / g)]

[0043] [Table 1]

[0044] <Production Example 1: Production of sodium polyacrylate (B-2)> 500 parts of ion-exchanged water was charged into a reaction vessel equipped with a stirrer, a dropping funnel, a nitrogen gas inlet tube, a thermometer and a reflux condenser, and the inside of the system was replaced with nitrogen gas while stirring, and the temperature was raised to 85°C. At the same temperature (85°C), a mixture of 200 parts of acrylic acid, 0.07 parts of dodecyl mercaptan, 1.4 parts of 2,2'-azobis(2,4-dimethylvaleronitrile), and 16 parts of isopropyl alcohol was dropped over 3 hours, and further reacted at the same temperature for 1 hour. After the reaction, the mixture was cooled to 30°C, and 396 parts of 28% NaOH water was added to adjust the pH to 10.0, and then further diluted with 1063 parts of ion-exchanged water to obtain a diluted solution containing sodium polyacrylate (B-2). The weight average molecular weight of sodium polyacrylate (B-2) was 1,000,000, and the solid content in the diluted solution was 12%.

[0045] <Production Example 2: Production of polyacrylic acid sodium crosslinked polymer (B-3)> 0.01 parts of hydrogen peroxide and 0.02 parts of ascorbic acid were added to 1,000 parts of an aqueous solution containing 25% of monomer components consisting of 72 mol% sodium acrylate, 27.95 mol% acrylic acid, and 0.05 mol% N,N-methylenebisacrylamide, and the mixture was adiabatically polymerized in a nitrogen atmosphere at a polymerization initiation temperature of 10°C for 5 hours to obtain a gel-like polymer. This gel-like polymer was dried in a belt-type hot air dryer set at 150°C, and then pulverized to a particle size of 20 to 60 mesh to obtain a polyacrylic acid Na crosslinked polymer (B-3). The polyacrylic acid Na crosslinked polymer (B-3) was not dissolved in water, and the weight average molecular weight was not measurable.

[0046] <Production Example 3: Production of polyacrylic acid sodium crosslinked polymer (B-4)> The same procedure as in Production Example 2 was carried out except that the gel polymer was pulverized to a particle size of 60 to 150 mesh to obtain a poly(Na acrylate) crosslinked polymer (B-4). (B-4) was not dissolved in water, and the weight average molecular weight was not measurable.

[0047] <Production Example 4: Production of starch-acrylic acid copolymer (B-5)> 10 parts of corn starch, 200 parts of water, and 1,000 parts of methanol were charged into a reaction vessel equipped with a stirring rod, a nitrogen inlet tube, and a thermometer, and stirred at 50°C for 1 hour under nitrogen gas flow. After cooling to 30°C, 20 parts of acrylic acid, 80 parts of sodium acrylate, 1 part of N,N-methylenebisacrylamide, and 0.5 parts of azobisvaleric acid as a polymerization catalyst were added, and polymerization was carried out by stirring at 60°C for 6 hours, resulting in a white suspension [I]. The powder obtained after filtering this white suspension [I] was washed with a water-methanol mixed solution (water to methanol weight ratio 2:10), dried under reduced pressure at 60°C for 3 hours, and then pulverized to obtain 49 parts of powdered starch-acrylic acid copolymer (B-5). The starch-acrylic acid copolymer (B-5) did not dissolve in water, and the weight average molecular weight could not be measured.

[0048] <Production Example 5: Production of acrylic acid copolymer (B-6)> 240 parts of ion-exchanged water was charged into a reaction vessel equipped with a stirrer, a dropping funnel, a nitrogen gas inlet tube, a thermometer and a reflux condenser, and the inside of the system was replaced with nitrogen gas under stirring, and the temperature was raised to 85°C. At the same temperature, a mixture of 87.4 parts of acrylic acid, 130.1 parts of hydroxyethyl methacrylate, 4.9 parts of dodecyl mercaptan, 0.6 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) and 16 parts of isopropyl alcohol was dropped over 3 hours, and further reacted at the same temperature for 1 hour. After the reaction, the product obtained was cooled to 30°C, and 73 parts of 28% NaOH water was added to adjust the pH to 6.0, to obtain an acrylic acid-based copolymer (B-6). The weight average molecular weight of the acrylic acid-based copolymer contained in the acrylic acid-based copolymer (B-6) was 12,000, and the solid content in the polymer was 40%.

[0049] <Comparative Production Example 1: Production of Acrylic Acid Copolymer (B'-2)> An acrylic acid-based copolymer (B'-2) was obtained in the same manner as in Production Example 5, except that the amount of acrylic acid was changed to 43.2 parts and the amount of hydroxyethyl methacrylate was changed to 169.2 parts in Production Example 5. The weight average molecular weight of the acrylic acid-based copolymer contained in the acrylic acid-based copolymer (B'-2) was 15,000 and the solid content was 40%.

[0050] <Method for measuring weight-average molecular weight of (co)polymer> The weight average molecular weights of the (co)polymers obtained in the Production Examples and Comparative Production Examples were measured by gel permeation chromatography (GPC) under the following conditions. (Measurement conditions) Apparatus: Gel permeation chromatography ["HLC-8120GPC", manufactured by Tosoh Corporation] Column: "TSKgel G6000PWxl" and "TSKgel G3000PWxl" [both manufactured by Tosoh Corporation] connected in series. Eluent: 0.5% by weight of sodium acetate dissolved in methanol / water = 30 / 70 (volume ratio) Reference material: Polyethylene glycol (hereinafter abbreviated as PEG) Injection conditions: sample concentration 0.25 wt%, column temperature 40°C

[0051] <Method of measuring solid content> The solids contents of compound (B) [(B-1 to (B-6)] and compound (B') [(B'-1), (B'-2)] were measured by the following method. 1 g of sample was weighed out precisely into an aluminum cup (container weight: T) whose weight was measured to four decimal places using a precision balance, and the sample weight before drying (S) was recorded. The aluminum cup containing 1 g of sample was placed in a hot air circulation dryer heated to 130°C, dried for 45 minutes, removed, and the total weight after drying (G) was weighed out precisely. The solid content was calculated from the following formula: Solid content (%) = [{total weight after drying (G) - container weight (T)} / sample weight before drying (S)] x 100

[0052] <Method for calculating the total amount of carboxyl groups and carboxylate salt groups contained in compound (B) [(B-1 to (B-6)] and compound (B') [(B'-1) to (B'-2)]> (1) A sample was placed in a beaker and its weight (1 g) was precisely measured. 50 ml of ion-exchanged water was added and stirred to dissolve or swell the sample, thereby obtaining a sample solution. (2) Immerse the electrodes of the potentiometric titrator in the sample solution. While stirring at a speed that does not cause the solution to splash outside the beaker, add a mixture of reagent grade hydrochloric acid (35%) and ion-exchanged water (35% hydrochloric acid: ion-exchanged water = 1:1) with a dropper until the pH of the sample solution is below 3. (3) 0.1 mol / L potassium hydroxide methanol standard solution was added little by little, and the mixture was stirred until the potential difference became constant. The potential difference and the amount of the drop were recorded when the potential difference became constant. This operation was repeated until the end point was passed. The endpoint was determined by plotting the amount of the standard solution dropped and the potential difference on a graph paper, and the inflection point of the titration curve was determined as the endpoint. (4) The procedures (1) to (3) were carried out on two samples, and a blank test was also carried out. The total amount of carboxyl groups and carboxylate groups contained in the molecule was calculated from the following formula, and the average value of the two samples was taken as the total amount of carboxyl groups and carboxylate groups contained in the molecule (mmol / g). Total amount of carboxyl groups and carboxylate groups contained in the molecule (mmol / g) = (AB) × f × 0.1 / S A: The amount (ml) of 0.1 mol / L potassium hydroxide methanol standard solution required for this test B: Amount of 0.1 mol / L potassium hydroxide methanol standard solution dropped for blank test (ml) f: Potency of 0.1 mol / L potassium hydroxide methanol standard solution S: Sample amount (g)

[0053] [Table 2]

[0054] <Examples 1 to 13, Comparative Examples 1 to 5> Fertilizers of the examples and comparative examples were prepared and subjected to the following evaluation tests.

[0055] <Evaluation test 1: pH of the supernatant after phosphoric acid recovery> The pH of the supernatant was measured using the following equipment under the following conditions. The results are shown in Table 3 or Table 4. Equipment used for pH measurement: Portable pH meter D-71 (HORIBA) Measurement conditions: 25±2℃ It is preferable that the pH of the supernatant is 6.0 to 9.0, since the neutralization step is not essential.

[0056] <Evaluation test 2: Percentage of water-soluble phosphorus (phosphate)> (1) Calculation of phosphorus concentration in the mixed liquid The phosphorus concentration in the mixed solution [mixture of substance (A), compound (B) or compound (B'), and ion-exchanged water] obtained in the Examples and Comparative Examples was calculated by the following formula. [Phosphorus concentration in the mixed solution (ppm)] = [Amount of substance (A) charged (g)] × [Total phosphorus concentration of substance (A) (mgP / g)] × 10 (2) Calculation of the water-soluble ratio of phosphorus (ratio of phosphate) The water-solubilized phosphorus ratio in the filtrate obtained in the Examples and Comparative Examples was calculated by the following formula. The results are shown in Table 3 or Table 4. [Water-soluble phosphorus ratio (%)] = 100 × {[Phosphate concentration of the filtrate (ppm)] / [Phosphorus concentration in the mixed solution (ppm)]} A high water-soluble ratio of phosphorus is preferable, specifically, 0.2% or more.

[0057] Example 1 In a 100 ml glass beaker, 1 part of aluminum phosphate (A-1) as a substance containing poorly soluble phosphate and 0.03 parts of sodium polyacrylate (B-1) [Sanyo Chemical Industries, Ltd., Carrybon N-400] as a polymer compound (B) containing 5 mmol / g or more of carboxylic acid groups in the molecule were weighed and mixed to obtain a mixture, and then 99 parts of ion-exchanged water was added and the mixture was shaken lightly to obtain a mixed liquid. The mixed liquid was left to stand at room temperature of 25°C for 3 hours. The supernatant was filtered using a 2.5 ml Thermo syringe fitted with a 0.45 μm syringe filter, and the filtrate was collected. The concentration of phosphate phosphorus in the filtrate was measured using Packtest(R) Phosphate / Phosphorus Phosphate WAK-PO4 (Kyoritsu Chemical Research Institute) and a spectrophotometer. The concentration of phosphate phosphorus in the filtrate was 10 ppm. In addition, the pH of the supernatant remaining in the beaker after collecting the filtrate (supernatant after releasing the phosphoric acid) was measured, and the pH was 7.5.

[0058] Example 2 0.5 parts of aluminum phosphate (A-1) as a substance containing poorly soluble phosphate and 0.03 parts of sodium polyacrylate (B-1) as compound (B) were weighed and mixed in a 100 ml glass beaker to obtain a mixture, and then 99 parts of ion-exchanged water was added and the mixture was gently shaken to obtain a mixed liquid. The beaker was immersed in a water bath at 50°C and left to stand for 3 hours. The supernatant was sucked into a 2.5 ml thermosyringe, and a 0.45 μm syringe filter was attached to recover the filtrate. The concentration of phosphorus in the filtrate was measured in the same manner as in Example 1, and the concentration of phosphorus in the filtrate was 26 ppm. In addition, the pH of the supernatant remaining in the beaker after recovering the filtrate was measured in the same manner as in Example 1, and the pH was 7.5.

[0059] Example 3 The same operation as in Example 1 was carried out except that 0.03 parts of a polyacrylic acid Na crosslinked polymer (B-4) was added instead of polyacrylic acid Na (B-1) to obtain a mixture, and the time for leaving the mixture and water was changed from 3 hours to 1 week. In addition, the phosphoric acid concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphoric acid concentration of the filtrate was 35 ppm, and the pH of the supernatant was 7.0.

[0060] Example 4 0.1 parts of aluminum phosphate (A-1) as a substance containing poorly soluble phosphate and 0.03 parts of polyacrylic acid Na crosslinked polymer (B-4) as compound (B) were weighed and mixed in a 100 ml glass beaker to obtain a mixture, and then 99 parts of ion-exchanged water was added and the mixture was shaken lightly to obtain a mixed liquid. The beaker containing the mixed liquid was immersed in a water bath at 80°C and left to stand for 3 hours. The supernatant was sucked into a 2.5 ml thermosyringe, and a 0.45 μm syringe filter was attached to recover the filtrate. The concentration of phosphorus in the filtrate was measured in the same manner as in Example 1, and the concentration of phosphorus in the filtrate was 30 ppm. In addition, the pH of the supernatant remaining in the beaker after recovering the filtrate was measured in the same manner as in Example 1, and the pH of the supernatant was 7.0.

[0061] Example 5 The same operations as in Example 1 were carried out, except that 1 part of iron(III) phosphate dihydrate (A-2) was added instead of aluminum phosphate (A-1) and 0.03 parts of sodium polyacrylate (B-2) was added instead of sodium polyacrylate (B-1). In addition, the phosphorus phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphorus phosphate concentration of the filtrate was 12 ppm and the pH of the supernatant was 9.0.

[0062] Example 6 The same operations as in Example 1 were carried out, except that 1 part of tricalcium phosphate (A-3) was added instead of aluminum phosphate (A-1) and 0.03 parts of sodium polyacrylate crosslinked polymer (B-3) was added instead of sodium polyacrylate (B-1). In addition, the phosphorus phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphorus phosphate concentration of the filtrate was 11 ppm and the pH of the supernatant was 7.0.

[0063] Example 7 The same procedure as in Example 4 was carried out, except that one part of rice husk charcoal (A-4) was added instead of aluminum phosphate (A-1). In addition, the phosphate phosphorus concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphate phosphorus concentration of the filtrate was 3 ppm, and the pH of the supernatant was 8.4.

[0064] Example 8 The same operations as in Example 4 were carried out, except that 1 part of chicken manure charcoal (A-5) was added instead of aluminum phosphate (A-1) and 0.03 parts of starch-acrylic acid copolymer (B-5) was added instead of sodium polyacrylate crosslinked polymer (B-4). In addition, the phosphate phosphorus concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphate phosphorus concentration of the filtrate was 55 ppm and the pH of the supernatant was 9.0.

[0065] Example 9 The same procedure as in Example 4 was carried out, except that one part of soil (A-6) was added instead of aluminum phosphate (A-1). In addition, the phosphate phosphorus concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1. The phosphate phosphorus concentration of the filtrate was 2 ppm, and the pH of the supernatant was 7.3.

[0066] Example 10 The same operation as in Example 1 was carried out, except that acrylic acid-based copolymer (B-6) was added in an amount of 0.03 parts in terms of solid content instead of sodium polyacrylate (B-1) in Example 1. In addition, the phosphorus phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphorus phosphate concentration of the filtrate was 5 ppm, and the pH of the supernatant was 6.0.

[0067] Example 11 The same operation as in Example 4 was carried out, except that sodium polyacrylate (B-1) was added in an amount of 0.1 parts in terms of solid content instead of sodium polyacrylate crosslinked polymer (B-4) in Example 4. In addition, the phosphorus phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphorus phosphate concentration of the filtrate was 28 ppm, and the pH of the supernatant was 7.6.

[0068] Example 12 The same operation as in Example 4 was carried out, except that sodium polyacrylate (B-1) was added to give a solid content of 0.002 parts in Example 1. In addition, the phosphorus phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1. The phosphorus phosphate concentration of the filtrate was 5 ppm, and the pH of the supernatant was 7.3.

[0069] (Example 13) The same operations as in Example 1 were carried out except that 1 part of soil (A-7) was added instead of aluminum phosphate (A-1), 0.03 parts of sodium polyacrylate crosslinked polymer (B-3) was added instead of sodium polyacrylate (B-1), and the mixture was allowed to stand for 24 hours at 10° C. In addition, the phosphate phosphorus concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1. The phosphate phosphorus concentration of the filtrate was 2 ppm, and the pH of the supernatant was 7.5.

[0070] Comparative Example 1 The same operation as in Example 3 was carried out, except that 0.03 parts of carboxymethylcellulose Na (B'-1) was added instead of polyacrylic acid Na crosslinked polymer (B-4) in Example 3. In addition, the phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphate concentration of the filtrate was 2 ppm, and the pH of the supernatant was 7.1.

[0071] Comparative Example 2 The same operation as in Example 1 was carried out, except that acrylic acid-based copolymer (B'-3) was added in an amount of 0.03 parts in terms of solid content instead of sodium polyacrylate (B-1) in Example 1. In addition, the phosphorus phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was recovered were measured in the same manner as in Example 1, and the phosphorus phosphate concentration of the filtrate was 2 ppm, and the pH of the supernatant was 6.9.

[0072] Comparative Example 3 The same procedure as in Example 9 was carried out, except that 0.03 parts of carboxymethyl cellulose (B'-1) was added instead of the sodium polyacrylate crosslinked polymer (B-4) in Example 9. In addition, the phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1, and the phosphate concentration of the filtrate was 0.1 ppm, and the pH of the supernatant was 6.9.

[0073] Comparative Example 4 The same procedure as in Example 9 was carried out except that the polyacrylic acid Na crosslinked polymer (B-4) was not used. In addition, the phosphorus phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1. The phosphorus phosphate concentration of the filtrate was 0.1 ppm, and the pH of the supernatant was 6.0.

[0074] Comparative Example 5 The same procedure as in Example 13 was carried out except that the polyacrylic acid Na crosslinked polymer (B-3) was not used. In addition, the phosphorus phosphate concentration of the filtrate and the pH of the supernatant remaining in the beaker after the filtrate was collected were measured in the same manner as in Example 1. The phosphorus phosphate concentration of the filtrate was 0 ppm, and the pH of the supernatant was 6.0.

[0075] [Table 3]

[0076] [Table 4]

[0077] As shown in Tables 3 and 4, the example products containing a substance containing poorly soluble phosphate and a polymer compound having a total amount of carboxyl groups and carboxylate groups contained in the molecule of 5 mmol / g or more had a higher water-solubilization rate of phosphorus than the comparative example products. In other words, it can be seen that phosphoric acid is efficiently dissolved into water simply by using the example products containing a substance containing poorly soluble phosphate and a polymer compound having a total amount of carboxyl groups and carboxylate groups contained in the molecule of 5 mmol / g or more in an environment where water is provided. The phosphoric acid dissolved into water is phosphate ion and / or available phosphoric acid, which is a component that can be absorbed by plants and function as a fertilizer. Furthermore, since the pH of the supernatant after liberating phosphoric acid from the example products is in the range of 6 to 9, according to the present invention, a step of returning the liquid after liberating phosphoric acid to neutral is not essential. That is, according to the present invention, a substance containing a poorly soluble phosphate and a compound having a total amount of carboxyl groups and carboxylate groups in the molecule of 5 mmol / g or more can be made to function as a fertilizer simply by using the substance in an environment where water is provided. As a result, it is found that the fertilizer of the present invention is a fertilizer obtained by a safe and simple method.

Claims

1. The present invention includes a substance containing a poorly soluble phosphate and a polymer compound having a carboxyl group and / or a carboxylate group in the molecule, A fertilizer in which the total amount of carboxyl groups and carboxyl groups contained in the polymer compound having carboxyl groups and / or carboxyl groups in the molecule is 5 mmol / g or more.

2. 2. The fertilizer according to claim 1, wherein the polymer compound having a carboxy group and / or a carboxylate group in the molecule is a polymer containing structural units derived from (meth)acrylic acid and / or a (meth)acrylate salt.

3. The fertilizer according to claim 1 or 2, further comprising water mixed therein.

4. The method includes step 1 of mixing a component containing a substance containing a poorly soluble phosphate and a polymer compound having a carboxy group and / or a carboxylate group in the molecule, The polymer compound having a carboxy group and / or a carboxylate group in its molecule has a total amount of 5 mmol / g or more of carboxylate groups.

5. 5. The method for producing a fertilizer according to claim 4, wherein the polymer compound having a carboxy group and / or a carboxylate group in the molecule is a polymer containing structural units derived from (meth)acrylic acid and / or a (meth)acrylate salt.

6. 6. The method for producing a fertilizer according to claim 4 or 5, wherein in step 1, water is further added to the components and mixed.

7. 7. The method for producing a fertilizer according to claim 6, further comprising a step of allowing the mixture obtained by adding water to and mixing the components in step 1 to stand at a temperature condition of 10°C to 80°C.

Citation Information

Patent Citations

  • JP1973075330A

  • Katsuseiodeinoshiryoka aruiha hiryokaho

    JP1976027577A

  • Method and composition for promoting plant growth

    JP1986256991A

  • Water content regulator for garbage disposal and garbage disposal method

    JP2004261662A

  • Granulation assisting agent for slag

    JP2007217247A